Intimidade e vida privada: uma necessária distinção para a correta proteção aos direitos da personalidade - Maurmo, Julia Gomes Pereira (2012)
The present essay s central object is to shed light over the differentiation, brought by the Federal Constitution of 1988, between the institutes of intimacy and private life, as well as the legal consequences of such distinction. In order to achieve that, it was intended to build the historical evolution of the personality rights, with the formation of the person, the human dignity corollaries and its freedom, as well as its placing on international legal diplomas, and on the Brazilian Constitutions. Next, it was intended to conceptualize privacy as a genre of which intimacy and private life are species. Finally, it was aimed to demonstrate that both the homeland doctrine and jurisprudence misunderstand such institutes, which hinders an adequate judicial protection, as well as prevents the correct quantification of the moral damage resulting from the violation of such rights